2008
DOI: 10.3390/ijms9050698
|View full text |Cite
|
Sign up to set email alerts
|

Caffeine Induces Cell Death via Activation of Apoptotic Signal and Inactivation of Survival Signal in Human Osteoblasts

Abstract: Caffeine consumption is a risk factor for osteoporosis, but the precise regulatory mechanisms are currently unknown. Here, we show that cell viability decreases in osteoblasts treated with caffeine in a dose-dependent manner. This cell death is attributed primarily to apoptosis and to a smaller extent, necrosis. Moreover, caffeine directly stimulates intracellular oxidative stress. Our data support caffeine-induced apoptosis in osteoblasts via a mitochondria-dependent pathway. The apoptotic biochemical changes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
72
1
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(78 citation statements)
references
References 60 publications
3
72
1
2
Order By: Relevance
“…Some studies indicated that the viability of osteoblasts was significantly decreased at concentrations >0.5 mM caffeine, 9 and the formations of osteoblast and mineralization were significantly decreased in the presence of 10 mM caffeine. 8 These findings indicated that high concentrations of caffeine may possess the cytotoxicity to osteoblasts and its precursor cells.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies indicated that the viability of osteoblasts was significantly decreased at concentrations >0.5 mM caffeine, 9 and the formations of osteoblast and mineralization were significantly decreased in the presence of 10 mM caffeine. 8 These findings indicated that high concentrations of caffeine may possess the cytotoxicity to osteoblasts and its precursor cells.…”
Section: Discussionmentioning
confidence: 99%
“…Possibly in CAF group there was greater plasma concentration of caffeine compared to the CO group, consequently higher bioavailability during the healing process after tooth extraction. This increased supply in the repair site possibly led to changes in intracellular mediators and thus to a lower viability and activity of osteoblasts to synthesize bone matrix, as evidenced in several studies (8,20,21), and also higher osteoclastic activity (19), which may have provided low maturity of bone trabeculae with the use of pure caffeine (Figs. 1F, I).…”
Section: Discussionmentioning
confidence: 99%
“…The quality evaluation of bone repair process in the dental socket of animals treated with coffee or caffeine revealed that the newly formed bone trabeculae did not have suitable maturity even on 21 st Many studies have demonstrated that caffeine acts directly on osteoblasts and osteocytes disturbing the process of differentiation (20) multiplication (9), bone matrix production and mineralization (20), even leading to apoptosis of these cells (21). In osteoclasts, it is suggested that the presence of caffeine may increase the differentiation of these cells with the consequent decrease of bone mineral density (19).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…None of the participants had a history of either smoking or taking medications. Subjects were instructed to refrain from alcohol (Taylor et al 2010b), caffeine (Lu et al 2008), smoking (Anbarasi et al 2006), and intense physical activity before and on the test day and until the 4-h post-exercise sampling was completed. On the experimental days, all subjects arrived at the laboratory at either 6:30 or 7:30 am after an overnight fast.…”
Section: Subjectsmentioning
confidence: 99%